Wi-Fi HaLow for the Internet of Things: An up-to-date survey on IEEE 802.11ah research. (15th May 2021) - Tian, Le; Santi, Serena; Seferagić, Amina; Lan, Julong; Famaey, Jeroen
Abstract: IEEE 802.11ah, marketed as Wi-Fi HaLow, is a new sub-1GHz Wi-Fi technology for the Internet of Things (IoT), aiming to address the major challenge of the IoT: providing connectivity among a large number of power-constrained stations deployed over a wide area. In order to achieve this goal, several novel features are introduced in IEEE 802.11ah in both the Physical Layer (PHY) and Media Access Control (MAC) layer. These features have been extensively studied from various perspectives in the past years. To provide readers with an insight into these novel features, this article provides an overview of the IEEE 802.11ah technology and conducts a comprehensive summary and analysis on the related research, revealing how to utilize these novel features to satisfy the demanding IoT performance criteria. Furthermore, the remaining issues that need to be addressed to fully realize the vision of large-scale and low power Wi-Fi networks for the IoT are discussed.